Sport and Exercise Science - Merc, Matjaz (IntechOpen, 2018)
Professional and semiprofessional sports as well as excessive amateur exercise inevitably lead to some degree of musculoskeletal injury once in a sportsman's career. Some injuries are represented as chronic injuries, which can result in irreversible long-term tissue changes and deformities. The subject of this book is to represent the up-to-date knowledge about etiology, pathogenesis, diagnosis, management, and prevention of chronic injuries or sport-related long-term changes in locomotor system.